A Biocentric Ontology at the Basis of an Anthropocentric Concept of Co-Responsibility to Non-Human World - Battistoni, Giulia (Filosofia Morale/Moral Philosophy, 2024)
Starting from the Australian case Sharma v. Minister for the Environment this paper discusses the concept of responsibility in the face of current environmental challenges, showing that the traditional concept of a retrospective, causal, individual responsibility is not able to account for secondary consequences of human actions on future generations and on the environment. This leads to the urgent elaboration of a wider concept of responsibility, which the paper sets out to discuss and to which it offers suggestions.